2006
DOI: 10.1002/cvde.200604219
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Octadecyltrimethoxysilane Monolayers Enabling Selective‐Area Atomic Layer Deposition of Iridium

Abstract: Atomic layer deposition (ALD) [1,2] is an excellent tool for atomic-level materials engineering. In ALD, a thin film is grown in a self-limiting manner through surface reactions between alternately supplied gaseous precursors. The ALD technique enables variation of the film composition with atomic-layer accuracy. However, this accuracy is only limited naturally in the growth direction, i.e., perpendicular to the substrate surface. With selective-area ALD, the film growth could also be controlled on the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 16 publications
0
49
0
Order By: Relevance
“…Färm et al 56,58 successfully demonstrated a preparation method for the passivation and patterning of octadecyltrimethoxysilane (CH 3 (CH 2 ) 17 Si(OCH 3 ) 3 self-assembled monolayers (SAM) for the prevention of iridium ALD process at 225 C with Ir(acac) 3 and O 2 as precursors. This research seems to be the rst attempt to grow iridium by selective-area ALD using a patterned SAM.…”
Section: 52mentioning
confidence: 99%
See 1 more Smart Citation
“…Färm et al 56,58 successfully demonstrated a preparation method for the passivation and patterning of octadecyltrimethoxysilane (CH 3 (CH 2 ) 17 Si(OCH 3 ) 3 self-assembled monolayers (SAM) for the prevention of iridium ALD process at 225 C with Ir(acac) 3 and O 2 as precursors. This research seems to be the rst attempt to grow iridium by selective-area ALD using a patterned SAM.…”
Section: 52mentioning
confidence: 99%
“…Complete experimental conrmation of this scheme can be found in ref. 32 and nanotechnology 56,58,118 applications. In this section we focus on the features of thin lm growth on complicated 3D structures that is important for microelectronics and nanotechnology applications.…”
mentioning
confidence: 99%
“…65 For example, SAMs have been shown to be effective masking agents for the ALD of HfO 2 , 66 Pt, 67 TiO 2 , 68 ZrO 2 , 69 ZnO, 70 Ir, 71 Co, 72 and Ru, 73 where in most cases a SAM with a uCH 3 termination was employed. A large fraction of this work does not involve growth on the organic but instead the use of a SAM to block the growth of an inorganic thin film.…”
Section: Introductionmentioning
confidence: 99%
“…To address this limitation, several researchers have investigated the formation of SAMs by vapor-phase deposition [50,52,62,[102][103][104][105]. The vapor phase provides several advantages over a liquid-phase process.…”
Section: Vapor-phase Depositionmentioning
confidence: 99%